Antiquity and Social Reform Religious Experience in the Unification Church, Feminist Wicca and Nation of Yahweh. - Hutchinson, Dawn. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2010)
Although religious innovation in America has historically been the norm rather than the exception, mainstream Americans have often viewed new religious movements Other suspicion and occasionally Other outright alarm. The question motivating many studies of new religious movements has been "why would someone join these religions?" In Antiquity and Social Reform, Dawn Hutchinson offers at least one answer to this often repeated query. She argues that followers of new religious movements in the 19...
Keywords: Unification Church; Nation of Yahweh; Experience (Religion); Wicca; RELIGION / Psychology of Religion; Electronic books